The social and environmental responsibility communication of Pos Indonesia regional 3 - Bakti, Iriana; Sjoraida, Diah Fatma; Wiyatna, Muhamad Fatah; Nugraha, Aat Ruchiat; Setianti, Yanti (Universitas Padjadjaran, 2025)
Background: Social and Environmental Responsibility (SER) represents the company’s commitment to supporting Sustainable Development Goals (SDGs). PT. Pos Indonesia Regional 3 West Java carried out social and environmental responsibilities under its policies. The SER program was established in collaboration with Universitas Padjadjaran through a farmer group empowerment program toward independent villages and food security in Cilembu Village, Pamulihan District, Sumedang Regency. Purpose: This research aimed to analyze SER communications by PT. Pos Indonesia Regional 3 West Java. Methods: It used a descriptive method. The data was collected through observation, interviews, and literature studies. Results: The results showed that the public relations department of PT. Pos Indonesia served as a communication facilitator in corporate social responsibility implementation through the farmer group empowerment program towards independent villages in Cilembu Pamulihan, Sumedang. Upon carrying out the SER activities, PT. Pos Indonesia held stages of situation recognition, collaboration, and collective action between stakeholders to produce an effective SER program. Conclusion: SER communication at PT. Pos Indonesia Regional 3 West Java consisted of internal communication, a report to company leaders and employees, and external communication for publicizing the company’s achievements. Implications: The success of social and environmental responsibility communication will depend on the role of public relations in a corporation.